PERAN MANAJEMEN MUTU ISO 9001 DALAM PENGELOLAAN KUALITAS SARANA DAN PRASARANA DI UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA, YOGYAKARTA - Putri, Musdalipah; Subiyantoro; Aflah Wahyuni Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the role of ISO 9001 quality management in managing the quality of facilities and infrastructure at Sunan Kalijaga State Islamic University (UIN), Yogyakarta. ISO 9001, as an international standard for quality management systems, provides a structured framework designed to enhance efficiency, effectiveness, and sustainability in the management of educational resources. The research employs a literature review method by analyzing journals, books, and official documents related to the implementation of ISO 9001 in the education sector, particularly within the context of Islamic higher education institutions. The analysis reveals that implementing ISO 9001 at UIN Sunan Kalijaga significantly improves the quality of facilities and infrastructure through a process-based approach, a focus on user satisfaction, and continuous evaluation and improvement. This standard enables the university to manage resources systematically, prioritize key needs, and ensure service sustainability. However, the implementation of ISO 9001 faces challenges such as limited staff understanding, resistance to organizational culture change, resource constraints, and complexities in documentation processes. The study concludes that despite these challenges, the application of ISO 9001 remains effective in improving the management of facilities and infrastructure at UIN Sunan Kalijaga. To support better implementation, the recommendations include enhancing staff training, allocating adequate resources, and optimizing technology to sustain the quality management system effectively.